The Need for Speed and Efficiency: A Brief Review of Small Molecule Antivirals for COVID-19 - Puhl, Ana C.; Lane, Thomas R.; Urbina, Fabio; Ekins, Sean (Frontiers in Drug Discovery, 2022)
While we currently have multiple highly effective vaccines approved for use against SARS-CoV-2 in the USA and other countries, there are far fewer small molecule antivirals approved to date. The emergence of the latest SARS-CoV-2 variant, Omicron which is heavily mutated in the spike protein, is also raising concerns about the effectiveness of these current vaccines and increasing the call for more therapeutic options. At the time of writing only remdesivir is approved by the FDA while molnupiravir (already approved in the United Kingdom) and Paxlovid (PF-07321332) have emergency use authorizations from the FDA. Repurposed molecules, such as dexamethasone and baricitinib, have been authorized for emergency use in some countries and are used in combination with remdesivir. After 2 years we are only now starting to see the progression of further molecules through animal models to assess their efficacy before clinical trials. As datasets accumulate from both in vitro and in vivo animal efficacy models, this may allow us to understand the physicochemical properties necessary for antiviral activity and enable the search for additional antivirals. We now summarize 25 small molecule drugs that are either approved, in the process of approval or in the pipeline for COVID which have both in vitro and in vivo data. We demonstrate that these drugs are structurally diverse and cover a wide chemistry space. This information may aid our understanding of what it takes to be a promising treatment for COVID-19 and propose how to discover antivirals faster and more efficiently for the next pandemic.